IN SEARCH OF POLYNESIAN ORIGINS: WITH SPECIAL REFERENCE TO LAPITA CULTURE - Timbul Haryono (Berkala Arkeologi, 1986)
The islands of Polynesia make up the largest group among the islands in the Pacific ocean. This group, in fact, consist of many islands forming a triangle. The main groups in the west are the Tongan, and Samoan and Ellice groups. The Cook, Society and Tuamotus lie in the east, with Easter Island as a far-off isolate, while the Hawaiian Islands and New Zealand are separated to the north and south respectively of the main west-east belt. The location of these islands between Asia in the west, Australia in the south and South America continent in the east is of considerable significance to the peopling and cultural development of the region. Many scholars have therefore been led to postulate the route of human movement into these scattered islands. Archaeological and anthropological researches have been carried out within the area to determine where the Polynesians originally come from. Various hypotheses have been proposed thereafter.